Implicit Employment Contracts: The Limits of Management Reputation for Promoting Firm Productivity - HALES, JEFFREY; WILLIAMSON, MICHAEL G. (Journal of Accounting Research, 2010)
ABSTRACT Implicit employment contracts are a common way to motivate firm productivity but also require that employees trust management to be fair when allocating postproduction firm resources between employees and owners. We use an experiment to study the problem of motivating firm productivity, which depends on levels of owner investment and employee productive effort, when managers have an incentive to favor the owner's interests over those of the employee. Drawing on research in psychology and behavioral economics, we argue that reputation concerns can more effectively promote firm productivity when manager compensation is relatively insensitive to how much the owner is allocated after production occurs. Consistent with our predictions, we find that reputation concerns lead to greater firm productivity and higher payoffs for all firm members, but only when manager pay is relatively insensitive to the owner's ex post allocation. In addition to offering testable empirical implications, our theory and results are important because they can help explain why executive compensation is, in practice, surprisingly insensitive to owner returns.